Associate Professor Dr. Tan Suat Hian produces Pro GoLive Multi Probiotic - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2021)
GAMBANG, 20 May 2021 - A researcher and lecturer from the Faculty of Industrial Sciences and Technology (FSTI), Universiti Malaysia Pahang (UMP), Associate Professor Dr. Tan Suat Hian, 38, produced Pro-GoLive: Multi-Probiotic.